2010
DOI: 10.1037/a0018351
|View full text |Cite
|
Sign up to set email alerts
|

An African American supervisor’s reflections on multicultural supervision.

Abstract: As the demographics of U.S. society become more diverse, more People of Color are attracted to the fields of counseling/clinical/school psychology and have the opportunity to work with supervisors from ethnically and culturally diverse backgrounds. An African American supervisor reflects on her experiences with multicultural supervision. Seven microaggression themes are discussed, along with three multicultural identity and competence disequilibrium patterns. The author also describes the benefits and challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…This supports a study by Pope-Davis et al (1995) that found a significant relationship existed between multicultural self-efficacy and ethnicity, with ethnic students showing a higher sense of competence than their White peers. According to Butler-Byrd (2010), White counsellor trainees “experience a great deal of disequilibrium, expressed as passive aggression, denial of differences, and/or of the significance of their own cultural/ethnic background and the backgrounds of others, or denial, guilt, and shame about their power and privilege” (p. 14). In addition, Parker and Schwarts (2002) suggest that White counsellors experience a sense of shame that may impede the advancement of multicultural competence.…”
Section: Discussionmentioning
confidence: 99%
“…This supports a study by Pope-Davis et al (1995) that found a significant relationship existed between multicultural self-efficacy and ethnicity, with ethnic students showing a higher sense of competence than their White peers. According to Butler-Byrd (2010), White counsellor trainees “experience a great deal of disequilibrium, expressed as passive aggression, denial of differences, and/or of the significance of their own cultural/ethnic background and the backgrounds of others, or denial, guilt, and shame about their power and privilege” (p. 14). In addition, Parker and Schwarts (2002) suggest that White counsellors experience a sense of shame that may impede the advancement of multicultural competence.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy‐five percent of the data set (18 of 24 articles) revealed that culturally competent supervisors needed to adopt many dynamic and purposeful positions, offering their supervisees clear instructions for discussing, analyzing, and applying multicultural principles and techniques in clinical practice. Several articles suggested supervisors who demonstrated openness to self‐reflection and exploration of personal biases and assumptions, honored and attended to all socio‐political‐cultural domains, and offered comfort and encouragement when needed greatly benefited the supervisees (Ancis & Marshall, ; Butler‐Byrd, ; Reynaga‐Abiko, ; Singh & Yuk Sim Chun, ).…”
Section: Resultsmentioning
confidence: 99%
“…Butler‐Byrd () defined essentials of advocacy as fostering supervisees’ awareness of the influences of power, privilege, and oppression and the dynamics of social groups in interpersonal, group, and systemic conflicts within social context. Twenty‐five percent of the articles (6 of 24) showed both supervisors and supervisees recognized the implications and challenges of having conversations about social justice and client‐centered advocacy in supervision (Ancis & Marshall, ; Butler‐Byrd, ; Field et al., ; Soheilian et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations